Green Packaging in Retailers: Case Studies on Lidl, Tesco and Waitrose - Hong, Mo-Yun (2020)
Environmental problems are one of the most serious problems facing contemporary society. Although sustainable development is not a new topic, greening has been developing and permeating almost every industry. Packaging is one of the elements of green development. There are many articles about green packaging, especially food packaging. However, the number of articles on the development of retailers' green packaging is relatively small. Packaging is a part of the retail industry and has been increasingly valued by customers in recent years. For this reason, retailers have taken various measures to develop green packaging.